2015
DOI: 10.1590/2317-1782/20152014053
|View full text |Cite
|
Sign up to set email alerts
|

Health and education: a partnership required for school success

Abstract: PURPOSE: To investigate the association between home environment resources and the school performance of children from a public school in Belo Horizonte, Brazil, enrolled in the fourth year of the second cycle of Elementary School. METHODS: This is a cross-sectional descriptive study in which 48 children aged between 8 and 12 years old participated. It included 28 boys, 20 girls, and their respective guardians. The children were evaluated in hearing and school performance regarding reading, writing, and arithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
(24 reference statements)
0
16
1
6
Order By: Relevance
“…Thus it is fundamental to study it in different populations of students (9,15) . In this study, the researched students were mostly belonging to the lower social classes and to families with few academic opportunities, reflected by low parental education, residents of an area with high levels of violence, factors that contribute to poor school performance (2,3,16) . Although there is an association between self-perception of reading and writing difficulties and the School Performance Test, 29% of the interviewed showed negative self-perception of reading and 40% showed inappropriate performance in the reading test, which shows that the self-perception is not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus it is fundamental to study it in different populations of students (9,15) . In this study, the researched students were mostly belonging to the lower social classes and to families with few academic opportunities, reflected by low parental education, residents of an area with high levels of violence, factors that contribute to poor school performance (2,3,16) . Although there is an association between self-perception of reading and writing difficulties and the School Performance Test, 29% of the interviewed showed negative self-perception of reading and 40% showed inappropriate performance in the reading test, which shows that the self-perception is not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that educators teach and encourage the self--determination skills (origin of the actions, learn from failures, greater well-being feeling) for students, regardless of family situation, personal difficulties or environmental characteristics, in order to enhance self-esteem, self-concept and academic performance, thus reducing school dropout rates and promoting, in the future, the social and professional insertion (9) . Studies that verified the relationship among the parenting practices and the student performance at school have shown that, when parents follow routinely school activities of the children, these ones have better performances (2,3,10) . Therefore, it is assumed that if those parents follow their children in school activities, they may also have better perception about their performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this, Ruijsbroek et al [30] in a study in the Netherlands demonstrated that parents' education and children's academic achievement are strongly positively related. Furthermore, a recent study in Brazil showed that low home environment resources is significantly associated with low academic success in primary school children [31]. Moreover, the school performance of children of affluent families was found significantly better compared with those of poor families in a study in Russia [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among the analyzed factors, one can mention the organization of the physical environment, the availability of educational materials, the activities performed by the child, parental involvement in the development process of children and educational family practices (10) . This instrument has been increasingly referenced in the areas of speech therapy, psychology and education for its high accuracy in the association with learning difficulties (11,12,13) . The assessment of reading processes is a challenging activity, due to the complexity of this task.…”
Section: Introductionmentioning
confidence: 99%